Incidencia de la disciplina en el desarrollo moral de los estudiantes de 3ro A de la escuela 20 de Enero, Parroquia Dr. Camilo Ponce, cantón Babahoyo provincia de los Ríos 2019 - Rivera, Elvira (2020)
What this research aims to analyze is to what degree does discipline affect the moral development of 3rd grade students at the January 20 school? It is considered that the undisciplined behavior that students have severely affects their interpersonal relationships. The disciplines of children usually have serious consequences, which do not allow a normal development disregarding it from school life, their personality tends to change for worse, for this reason in this investigation the factors that imply problems are investigated, scrutinizing in the family field of student. The variables addressed in the theoretical framework are a) Discipline b) Moral, in terms of research design a non-experimental transactional scheme since it does not receive any type of treatment, nor stimulation under any circumstances, 2 techniques are used which fully collaborate to The study of this case. Finally, it is concluded that the indiscipline presented by the students comes from the families, due to the lack of control on the part of the parents or the child's representative, with these foundations in all the above, it can be concluded by expressing that the parents are modelers in the behavior of the children and the way they relate, if the student does not develop in a pleasant and appropriate family context will not show adequate discipline.